Preparation of MoS2-coated three-dimensional graphene networks for high-performance anode material in lithium-ion batteries - Kong, Jing (2014)
A novel composite, MoS2-coated three-dimensional graphene network (3DGN), referred to as MoS2/3DGN, is synthesized by a facile CVD method. The 3DGN, composed of interconnected graphene sheets, not only serves as template for the deposition of MoS2, but also provides good electrical contact between the current collector and deposited MoS2. As a proof of concept, the MoS2/3DGN composite, used as an anode material for lithium-ion batteries, shows excellent electrochemical performance, which exhibits reversible capacities of 877 and 665 mAh g−1 during the 50th cycle at current densities of 100 and 500 mA g−1, respectively, indicating its good cycling performance. Furthermore, the MoS2/3DGN composite also shows excellent high-current-density performance, e.g., depicts a 10th-cycle capacity of 466 mAh g−1 at a high current density of 4 A g−1.